DZAWIL ARHAM'S LEGACY: The Urgency of Clear Arrangement In the Compilation of Islamic Law - Daulay, Mhd Nurhusein; Waruwu, Tri Eka Putra Mukhtarivanyah; Siswan, Heri; Ritonga, Nurman; Aljawi, Misnan (UIN Sumatera Utara, 2025)
Abstract: This study discusses the inheritance of dzawil arham (distant relatives) in the Compilation of Islamic Law (KHI) in Indonesia, which is identified as not regulated in existing regulations. Although KHI regulates the distribution of inheritance in detail for the closer heirs, the lack of clarity regarding inheritance rights for dzawil arham creates legal uncertainty in the implementation of inheritance distribution. This research aims to examine the importance of clearer arrangements regarding the inheritance rights of Dzawil Arham in KHI to provide legal certainty and justice for all related parties. Through a qualitative approach and normative analysis, it was found that more specific and detailed regulations regarding dzawil arham were needed so that the distribution of inheritance could be fairer and more equitable. This study recommends that KHI accommodate clearer rules related to the inheritance rights of dzawil arham, to ensure justice in the application of Islamic inheritance law in Indonesia.Keywords: Inheritance, Dzawil Arham, Compilation of Islamic Law, Distribution of Inheritance, Legal Certainty